More Is More in Language Learning: Reconsidering the Less‐Is‐More Hypothesis. (17th September 2018) - Brooks, Patricia J.; Kempe, Vera
Abstract: The Less‐Is‐More hypothesis was proposed to explain age‐of‐acquisition effects in first language (L1) and second language (L2) learning. We scrutinize different renditions of the hypothesis by examining how learning outcomes are affected by (a) limited cognitive capacity, (b) reduced interference resulting from less prior knowledge, and (c) simplified language input. While there is little to no evidence of benefits of limited cognitive capacity, there is ample support for a More‐Is‐More account linking enhanced capacity with better L1 and L2 learning outcomes and reduced capacity with childhood language disorders. Instead, reduced prior knowledge (relative to adults) may afford children greater flexibility in inductive inference; this contradicts the idea that children benefit from a more constrained hypothesis space. Finally, studies of child‐directed speech confirm benefits from less complex input at early stages but also emphasize how greater lexical and syntactic complexity of the input confers benefits in L1 attainment.